COMPARATIVE STUDY OF INDONESIAN AND UNITED KINGDOM LAWS ON THE NEGLIGENCE OF PET DOG OWNERS - Dwi Suparna, Brilian Albar; Wardhani, Novea Elysa; Fransisco (Hukum Responsif, 2025)
This study aims to analyze and find out the differences and similarities between Articles 1368, 1371 of the Civil Code and the Jurisdiction of The Dangerous Dogs Act, as well as to find out the problems and also efforts to find out the problems. The research method used is comparative descriptive research and the type of research used is the Normative Juridical research type. The results of the study show that there are similarities between the rules related to pet dogs in Indonesia and the United Kingdom in the form of points in Articles 1365, 1368, 1368, 1371 and the Dangerous Dogs Act. These rules show the absolute responsibility that the dog owner or person responsible for the behavior of the pet dog has. When it comes to harm prevention, both emphasize the importance of animal surveillance can be dangerous to others